The Parataxis and Hypotaxis in Recount Text Writing of Second-Grade Students at SMA Negeri 17 Medan - Gurusinga, Afridita Refina; Sinaga, Nenni Triana; Silitonga, Harpen (LPPPI Publishing, 2024)
This research aims to discover the parataxis and hypotaxis in recount text writing of second-grade students at SMA Negeri 17 Medan. This research uses qualitative research with an interactive model. In collecting data, this research employs observation and document analysis. Then, an interactive model for analyzing data has three steps: data condensation, data display, and conclusion/drawing verification. The research results show that the data findings on 15 students' recount text writings were found to use Parataxis can be seen by the appearance of 16 clauses, namely: 11 clauses “and”, 2 clauses “then”, 2 clauses “while”, 1 clause “but”, and 1 clause “before”. Hypotaxis found 21 clauses, namely: 12 clauses “after”, 3 clauses “because”, 5 clauses “when”, and 1 clause “which”. The study is essential for understanding how students construct sentences and organize their thoughts in recounting text. Parataxis involves the juxtaposition of clauses or sentences without subordinating them, while hypotaxis uses subordination to show the relationship between clauses.